واقع التعليم المفتوح في جامعة دمشق وسبل تطويره من وجهة نظر أعضاء الهيئة التعليمية: دراسة ميدانية في كليات التربية، الاقتصاد، الحقوق - حلاق، محمد أحمد (جامعة دمشق, 2017)
هدفت الدراسة إلى تعرف مشكلات التعليم المفتوح من وجهة نظر أعضاء الهيئة التعليمية في كليات: (الاقتصاد، الحقوق، التربية). وتعرف الفروق ذات الدلالة الإحصائية بين إجابات أفراد عينة الدراسة في درجة توافر مشكلات التعليم المفتوح من وجهة نظر أعضاء الهيئة التعليمية، يعزى إلى متغيرات: (الكلية، المرتبة العلمية، الملاك). والمقترحات لمواجهة مشكلات التعليم المفتوح من وجهة نظر أعضاء الهيئة التعليمية. واعتمد الباحث على المنهج الوصفي التحليلي. وبلغت عينة الدراسة (138) عضواً من أعضاء الهيئة التعليمية في ثلاث كليات هي: الاقتصاد، التربية، الحقوق. وطبق الباحث أداة الاستبانة. وخلصت الدراسة إلى النتائج الآتية: 1. عدم وجود فروق ذات دلالة إحصائية بين متوسط درجات إجابات أفراد عينة البحث على استبانة مشكلات التعليم المفتوح من وجهة نظر أعضاء الهيئة التعليمية، تعزى إلى متغير الملاك. 2. وجود فروق ذات دلالة إحصائية بين متوسط درجات إجابات أفراد عينة البحث على استبانة مشكلات التعليم المفتوح من وجهة نظر أعضاء الهيئة التعليمية، تعزى إلى متغير الكلية حيث ظهرت بين كليتي التربية والاقتصاد، لصالح كلية التربية. 3. عدم وجود فروق ذات دلالة إحصائية بين متوسط درجات إجابات أفراد عينة البحث على استبانة مشكلات التعليم المفتوح من وجهة نظر أعضاء الهيئة التعليمية، تعزى إلى متغير المرتبة العلمية.
The research aims to identify the problems of open education from the perspective of faculty members at colleges: (economics, law, education), and know the statistical significant differences between the answers of the research sample members about the availability of open learning problems from the perspective of the members of the faculty, due to the variables: (college, the scientific rank, owners). Proposals to address the problems of open education from the perspective of the members of the teaching staff. The researcher adopted the descriptive analytical method. The research sample consisted of (138) members of the teaching staff at three colleges: the economy, education, law. The researcher applied the questionnaire tool. The research found the following results: 1. There were no statistically significant differences between the average answers to the research sample to identify open education problems from the perspective of the members of the faculty members of the differences, attributable to owner's variable. 2. The presence of statistically significant differences between the average sample answers to a questionnaire open education problems from the perspective of the members of the faculty members, due to the college variable emerged between the faculties of education and the economy in favour of the College of Education. 3. The absence of any statistically significant differences between the average sample answers to a questionnaire open education problems from the perspective of the members of the faculty members due to the scientific rank variable.
Keywords: الإصلاح التعليمي -- التعليم المفتوح -- أعضاء هيئة التدريس -- جامعة دمشق